Immunomodulatory potential of Toxoplasma gondii lysate in C57BL/6 mouse model of autoimmune encephalomyelitis - Maryam Hajizadeh; Seyedmousa Motavallihaghi; Elham Badakhsh; Tohid Kazemi; Abdol Sattar Pagheh; Kareem Hatam-Nahavandi; Ehsan Ahmadpour (AMB Express)
Abstract Multiple sclerosis (MS) is a debilitating autoimmune disease characterized by chronic inflammation and demyelination within the central nervous system. Immunotherapy is an essential part of managing MS symptoms and progression. This study aimed to evaluate the immunomodulatory effects of Toxoplasma gondii lysate antigens (TLA) in a C57BL/6 mouse model of experimental autoimmune encephalomyelitis (EAE). Eighteen mice were randomly assigned into three groups: healthy controls, EAE-induced mice, and EAE-induced mice treated with TLA. Clinical scores were recorded daily for all mice. To assess immune responses, mRNA and protein expression levels in isolated splenocytes were measured using quantitative real-time PCR and ELISA, respectively. In addition, histological analyses were performed to evaluate inflammation and demyelination across the experimental groups. TLA-treated mice exhibited significantly reduced clinical scores and demyelination compared to the untreated EAE group. The treatment also decreased inflammatory cell infiltration in CNS tissues. At the molecular level, TLA modulated cytokine expression by downregulating pro-inflammatory markers (IFN-γ, IL-17, RORγT) and upregulating anti-inflammatory and regulatory markers (IL-4, GATA3, FOXP3, TGF-β, TNF-α). TLA treatment demonstrated immunomodulatory and neuroprotective effects in EAE mice, suggesting its potential as a prophylactic or therapeutic agent in MS. These findings support further exploration of parasitic antigens in the context of autoimmune neuroinflammatory diseases.